PENERAPAN DASAR-DASAR EKONOMI ISLAM DALAM KEHIDUPAN SEHARI-HARI MAHASISWA UNIVERSITAS ISLAM AL-IHYA DALAM MENCIPTAKAN PERILAKU MUAMALAH YANG SESUAI SYARIAT - Arief Rahman; Wahyuni, Neneng (Universitas Islam Al-Ihya Kuningan, 2024)
Studying Islamic economics is not only reserved for those studying Islamic economics or sharia banking. Every Muslim has an obligation to seek knowledge, including religious knowledge. As a comprehensive religion, Islam also contains teachings in economics so that every transaction or activity carried out does not deviate from sharia rules. The KSEI IMPAS Student Activity Unit (UKM) is a forum for friendship and education in introducing and deepening knowledge in Islamic economics. One of the programs is Islamic Economic Training with the aim of sharing knowledge which participants can participate in from various study programs, universities and the community. Before getting to know Islamic economics, what must first be understood is the basics of Islamic economics itself. It is hoped that this material can further broaden the horizons of study participants so that in the future, every economic activity carried out is followed by muamalah behavior that is in accordance with Islamic law.